(untitled) (Damascus University Journal for engineering sciences, 2023)
The materials importance in construction projects makes it necessary to track them from design stage to handling stage. Materials management is the plans, processes, and actions to track the materials along the project cycle. The problems related to supplying materials, tracking them during the implementation, and handling them are major challenges in construction projects. Through conducting surveys with construction projects managers in construction companies and engineering offices, this study highlights the aspects of the materials management in construction projects in Syria, through presenting how construction companies and engineering offices handle the materials and manage the construction site. Based on findings from the study, the procurement phase is the most challenging phase for effective materials management, which makes it the most affective phase among all the materials management phases. It also indicates the increase costs and delays in construction projects due to the reliance on traditional methods of tracking materials. This reflects the necessity of automating construction works, not only at the company level but also at the construction project sites level, through creating a system that can gather all the information related to the materials and give updates to track materials and take decisions in real-time.